Optimising vehicle performance with advanced active aerodynamic systems - Rijns, Steven; Teschner, Tom-Robin; Blackburn, Kim; Siampis, Efstathios; Brighton, James (Taylor & Francis, 2025)
This study investigates the performance potential of advanced active aerodynamic systems on high-performance vehicles. Static and active aerodynamic configurations, including asymmetrically actuated systems, are evaluated to identify performance gains and the mechanisms driving these improvements. Vehicle performance is optimised using a minimum lap time simulation framework, which utilises a transient vehicle dynamics model and CFD-derived aerodynamic data. Results indicate that configurations with greater aerodynamic adaptability enhance acceleration, braking, cornering, and straight-line performance, yielding notable lap time reductions compared to a static aerodynamic configuration. The asymmetrically controlled aerodynamic configuration achieves the highest lap time reduction of approximately 0.92 s (0.76%) due to its ability to modulate downforce both longitudinally and laterally. Optimal control strategies show that aerodynamic elements are actuated to balance vertical tyre load shifts resulting from load transfer, prioritising downforce on underloaded tyres in demanding scenarios like braking, cornering, and acceleration. Additionally, optimal design parameters for the brake, torque and roll stiffness distributions shift rearward as configurations provide greater control of aerodynamic loads on the rear axle. Overall, this research demonstrates the performance advantages of active aerodynamic systems and offers insights into the mechanisms underlying these enhancements, establishing a foundation for further innovations in the field.
Keywords: Active aerodynamics; performance optimisation; minimum lap time; optimal control; vehicle dynamics; computation fluid dynamics; 4007 Control Engineering, Mechatronics and Robotics; 40 Engineering; 4010 Engineering Practice and Education; 7 Affordable and Clean Energy; Automobile Design & Engineering; 49 Mathematical sciences